Liver protects neuron viability and electrocortical activity in post-cardiac arrest brain injury - Zhiyong Guo; Meixian Yin; Chengjun Sun; Guixing Xu; Tielong Wang; Zehua Jia; Zhiheng Zhang; Caihui Zhu; Donghua Zheng; Linhe Wang; Shanzhou Huang; Di Liu; et al. (EMBO Molecular Medicine)
Abstract Brain injury is the leading cause of mortality among patients who survive cardiac arrest (CA). Clinical studies have shown that the presence of post-CA hypoxic hepatitis or pre-CA liver disease is associated with increased mortality and inferior neurological recovery. In our in vivo global cerebral ischemia model, we observed a larger infarct area, elevated tissue injury scores, and increased intravascular CD45+ cell adhesion in reperfused brains with simultaneous hepatic ischemia than in those without it. In the ex vivo brain normothermic machine perfusion (NMP) model, we demonstrated that addition of a functioning liver to the brain NMP circuit significantly reduced post-CA brain injury, increased neuronal viability, and improved electrocortical activity. Furthermore, significant alterations were observed in both the transcriptome and metabolome in the presence or absence of hepatic ischemia. Our study highlights the crucial role of the liver in the pathogenesis of post-CA brain injury.